Association between patient age and the risk of mortality following local recurrence of a sacral chordoma. Issue 2 (22nd November 2019) - Houdek, Matthew T.; Hevesi, Mario; Schwab, Joseph H.; Yaszemski, Michael J.; Griffin, Anthony M.; Healey, John H.; Ferguson, Peter C.; Hornicek, Francis J.; Boland, Patrick J.; Sim, Franklin H.; Rose, Peter S.; Wunder, Jay S.
Abstract: Background: Local recurrence (LR) of sacral chordoma is a difficult problem and the mortality risk associated with LR remains poorly described. The purpose of this study was to evaluate the risk of mortality in patients with LR and determine if patient age is associated with mortality. Methods: A total of 218 patients (144 male, 69 female; mean age 59 ± 15 years) with sacrococcygeal chordomas were reviewed. Cumulative incidence functions and competing risks for death due to disease and nondisease mortality were employed to analyze mortality trends following LR. Results: The 10‐year overall survival (OS) was 55%. Patients with LR had 44% 10‐year OS, similar to patients without (59%; P = .38). The 10‐year OS between those less than 55 compared with ≥55 years were similar (69% vs 48%; P = .52). The 10‐year death due to disease was worse in patients with LR compared with those without (44% vs 84%; P < .001). In patients without LR, patients ≥55 years were 1.6‐fold more likely to experience death due to other causes. Conclusions: Patients with an LR are more likely to die due to disease. Advanced patient age was associated with higher all‐cause mortality following resection of sacral chordoma. LR of chordoma was associated with increased disease‐specific mortality, regardless of age.